Innovation and Nanotechnology: Converging Technologies and the End of Intellectual Property - Koepsell, David (Bloomsbury Publishing Plc, 2011)
This title presents explores how emerging nanotechnologies demand a new approach to scientific discovery. It develops a theory of authorship, artifacts and intentionality in relation to public policies and institutions. It concludes that localized manufacturing, distributed design and nanotechnology call into question intellectual property regimes.